The effect of NPK fertilizer and planting media on plant growth and saponin content of the medicinal plant Anchomanes difformis - REZA RAMDAN RIVAI; FITRI FATMA WARDANI; RIZMOON NURUL ZULKARNAEN (Smujo International, 2017)
Rivai RR, Wardani FF, Zulkarnaen RN. 2017. The effect of NPK fertilizer and planting media on plant growth and saponin content of the medicinal plant Anchomanes difformis. Nusantara Bioscience 9: 141-145. Anchomanes difformis (Blume) Engl., belongs to the aroid family (Araceae) and has potential as a medicinal plant. A. difformis has not in the past been widely cultivated by farmers in Indonesia, so if it is to be grown as a crop for medicinally active compounds, we must first find how best to cultivate it. The objective of the research described here was to determine an effective planting media and optimum dosage of a standard NPK fertilizer for A. difformis plant growth in pots, and saponin content of its rhizomes. The research was conducted at the Treub Laboratory and Garden Nursery, Center for Plant Conservation Botanic Gardens, Indonesian Institute of Sciences (LIPI). A completely randomized design with three replications was used to test a factorial arrangement of two treatment factors, namely: planting media of three types; and dosage of a standard NPK fertilizer (15% N, 15% P2O5, 15% K2O) at four levels. Results showed that for plant growth of Anchomanes difformis, a mixed medium of soil/cocopeat (1:1) was the best of the three media evaluated, and the application of the NPK fertilizer at a dosage equivalent to 100 kg/ha was the optimum fertilizer level. There was no statistical interaction between the treatment factors. The rhizomes of A. difformis had their highest level of saponin content when planted in the mixed soil/cocopeat (1:1) medium, and with NPK fertilizers at a dose level of 100 kg/ha.